Audit Sistem dan Teknologi Informasi berdasarkan COBIT 4.1 pada IT Marketing & Trading (M&T) PT Pertamina (Persero) Marketing Operation Region V Surabaya - Hanjani, Antonia Ratna; Sudarmaningtyas, Pantjawati; Sutomo, Erwin (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Abstract: PT Pertamina (Persero) MOR V have responsibility to some areas, such as East Java, Bali, NTB, NTT, and East Timor. This company have been established information and system technology services. IT Marketing and Trading has responsibility for 6 information and system technology services. Maturity level for the last audit process were good enough, but there are problems that exists. The problem that happened in these services are lack of response to customer in respond to customerâ€™s requests and lack of ERP and non-ERP services. Result from these problems is delays in management services called lack of services. The result is customerâ€™s trust to IT M&T could be reduced due to this lack of service. Because of that this company needs to do continuous information and system technology audit that based on the 2014 audit which has been done by this company. Hopefully this audit can be used to know the cause from these complaint. This audit used COBIT 4.1 standard because control for problems existed in this company have been identified using COBIT 4.1 so this company can continue to implement and monitor the accepted main goal has been reached or not.Â Keywords: audit, system and information technology audit. COBIT 4.1